Effects of different doses of dexmedetomidine combined with sufentanil in intravenous controlled analgesia after Salter osteotomy in children - He, Zhiwei; Ni, Huanhuan; Wang, Wei (Frontiers in Pediatrics, 2024)
Background This study aimed to investigate the effect of different doses of dexmedetomidine combined with sufentanil on postoperative analgesia in developmental hip dislocation in children after Salter osteotomy. Methods The clinical data of 98 children with developmental hip dislocation, who underwent Salter osteotomy in our center between January 2020 and February 2023, were selected. The children were randomly divided into four groups based on the application of patient-controlled intravenous analgesia (sufentanil + granisetron ± dexmedetomidine). All children received 1 µg/kg/day of sufentanil and 3 mg of granisetron. Group A did not receive dexmedetomidine, and Groups B, C, and D received 0.5, 0.75, and 1.0 µg/kg/day of dexmedetomidine, respectively. The pain indicators and immune factor levels of children in each group were compared. Results The heart rate (HR) and respiratory rate (RR) 2 h after operation in Groups C and D were significantly lower than those in Groups A and B (P < 0.05). The pain scores decreased over time after treatment in all groups. When compared at the same time point, children in Group D had the lowest pain scores, which were significantly lower than the other three groups (P < 0.05). The total consumption of sufentanil in Groups C and D was significantly lower than that in Group A (P < 0.05). On the first day after surgery, the children in Group D had lower levels of serum adrenocorticotropic hormone, interleukin-6, and corticosterone than those in Group A (P < 0.05). Conclusion Administration of 1.0 µg/kg/day of dexmedetomidine combined with sufentanil in intravenous controlled analgesia after Salter osteotomy for developmental hip dislocation in children has a better analgesic effect, less consumption of sufentanil, and low incidence of opioid adverse reactions.